Living on the Move: Mobility, Religion and Exclusion of Eastern European Migrants in Rural Scotland - Sergei Shubin (Population, Space and Place, 2011)
The paper explores theoretical and practical issues related to spiritual mobility and engagement with Eastern European migrants in rural Scotland. It develops a complex understanding of migrant’s living on the move and its approach stresses the relational, uncertain and transformative character of their mobilities. It suggests adding a spiritual element to the analysis of transnational mobilities and explores the ways in which constellations of mobility and religion generate more-than-corporeal dislocations, generate virtual movement and create new imaginations of the migrants’ place in the world.